Effect of resonant magnetic perturbations on low collisionality discharges in MAST and a comparison with ASDEX Upgrade. (27th March 2015) - Kirk, A.; Suttrop, W.; Chapman, I.T.; Liu, Yueqiang; Scannell, R.; Thornton, A.J.; Orte, L. Barrera; Cahyna, P.; Eich, T.; Fischer, R.; Fuchs, C.; Ham, C.; et al.
Abstract: Sustained edge localized mode (ELM) mitigation has been achieved on MAST and AUG using resonant magnetic perturbations (RMPs) with various toroidal mode numbers over a wide range of low to medium collisionality discharges. The ELM energy loss and peak heat loads at the divertor targets have been reduced. The ELM mitigation phase is typically associated with a drop in plasma density and overall stored energy. In one particular scenario on MAST, by carefully adjusting the fuelling it has been possible to counteract the drop in density and to produce plasmas with mitigated ELMs, reduced peak divertor heat flux and with minimal degradation in pedestal height and confined energy. While the applied resonant magnetic perturbation field can be a good indicator for the onset of ELM mitigation on MAST and AUG there are some cases where this is not the case and which clearly emphasize the need to take into account the plasma response to the applied perturbations. The plasma response calculations show that the increase in ELM frequency is correlated with the size of the edge peeling-tearing like response of the plasma and the distortions of the plasma boundary in the X-point region. In many cases the RMPs act to increase the frequency of type I ELMs, however, there are examples where the type I ELMs are suppressed and there is a transition to a small or type IV ELM-ing regime.